Pharmaceutical dosage forms : Parenteral medications - Nema, Sandeep; Ludwig, John D. (London : Informa Healthcare, 2010)
'A historical perspective of injectable drug therapy, common routes of administration, and biopharmaceutics of NCEs and NBEs. - An in-depth discussion on the preformulation and formulation of small and large molecules, including ophthalmic dosage forms. - A presentation of parenteral primary packaging options - glass and plastic containers, as well as elastomeric closures. - A definitive chapter on container-closure integrity. - New chapters on solubility and solubilization, formulation of depot delivery systems and biophysical/biochemical characterization of proteins'--Provided by publisher.
Vol.1. formulation and packing vol 3. regulations, validation and the future
Rev. ed. of: Pharmaceutical dosage forms, parenteral medications. 2nd ed., rev. and expanded. c1992-1993.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Infusions, Parenteral -- standards; Dosage Forms -- standards; Drug delivery systems -- methods; Pharmaceutical preparations -- administration & dosage; Quality control; Medical -- Drug Guides; Medical -- Pharmacology; Medical -- Pharmacy; Medical -- Nursing -- Pharmacology; Parenteral solutions; Pharmaceutical technology; Electronic books